1988
DOI: 10.1152/jappl.1988.64.1.451
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of VO2 with impulse and step exercise in humans

Abstract: The constancy of the time course (i.e., dynamic linearity) of the O2 uptake (VO2) response to exercise was examined by testing the law of superposition on data from impulse and step work rate forcings. Two impulses (10 s at a 235-W increase above a 25-W base line, I-235; and 5 s at a 475-W increase above a 25-W base line, I-475), four steps (ST) (25-65 W, ST1; 65-105 W, ST2; 25-105 W, ST3; and 25-145 W, ST4), and the corresponding off-transient responses were performed six to eight times by each of five subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
1
31
1
Order By: Relevance
“…64 -66 Consequently, because (1) most important exercise responses (eg, cardiac output, oxygen uptake, minute ventilation, heart rate) during exercise in children have response times Ͻ1 minute; (2) work rate increment is typically Ͻ30 W/min in pediatric subjects; and (3) desired submaximal measurements (eg, cardiac output) take Ͻ15 seconds to be completed, valid submaximal physiological responses to ramp changes in work rate can be obtained if appropriate and careful data analysis is performed. [67][68][69][70] …”
Section: Progressive Incremental Cycle Ergometer Protocolsmentioning
confidence: 99%
“…64 -66 Consequently, because (1) most important exercise responses (eg, cardiac output, oxygen uptake, minute ventilation, heart rate) during exercise in children have response times Ͻ1 minute; (2) work rate increment is typically Ͻ30 W/min in pediatric subjects; and (3) desired submaximal measurements (eg, cardiac output) take Ͻ15 seconds to be completed, valid submaximal physiological responses to ramp changes in work rate can be obtained if appropriate and careful data analysis is performed. [67][68][69][70] …”
Section: Progressive Incremental Cycle Ergometer Protocolsmentioning
confidence: 99%
“…An impulse work load of 300 W was used for the following reasons. First, the maximum work rate of the ergometer used in this study was 300 W. Although this work rate can be set for a duration of 10 sec, as it was in a former study (Hughson et al, 1988), it takes a few seconds to attain 300 W. Thus, in order to obtain a clear effect of 300 W, we set the period of impulse work at 20 sec. The experiment was performed once a day and repeated three times on separate days.…”
Section: Methodsmentioning
confidence: 99%
“…oxygen uptake (VO2) responding to impulse work (Bakker et al, 1980;Hughson et al, 1988;Swanson, 1990;Whipp and Ward, 1991), and it has been demonstrated . that VO2 is composed of two components (phase I and phase II).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations